AYURVEDIC INTERVENTIONS IN AUTISM SPECTRUM DISORDERS –A CASE SERIES (International Journal of Ayurveda and Pharma Research, 2017)
The prevalence of Autism Spectrum Disorder has increased to 1in 68 children. With impaired social interactions, impaired language and stereotypic movements as the classic triad of the condition, this social stigma is known to have no satisfactory treatment options till now. Applied behavior analysis(ABA), yoga therapy , music therapy, nutritional modifications and certain drugs have shown improvements in some aspects of the disease in various case studies but a significant result has not yet attained. In Ayurveda all childhood autism cases come under the category of either Vatakaphajaunmada or Vatapaittikaunmada. A case series was developed with 10 cases having the following characteristics. The diagnosis of all the cases was done with Childhood Autism Rating Scale (CARS) and the treatment outcome was measured by Autism Treatment Evaluation Checklist (ATEC). Clinical features of Unmada were also considered for the diagnosis and assessment of all the cases. The Ayurvedic treatment protocols for the cases selected were according to Dosha predominance of the condition at that time. All of the children considered for the case series were receiving speech as well as psycho therapies and appropriate dietary advice and assessment was done after three months. The change in CARS score was highly significant at 0.05% level (P